Are Fossils Mineral or Cultural Heritage? The Perspective of Brazilian Legislation - Kuhn, Caiubi Emanuel Souza [UNESP]; Carvalho, Ismar de Souza; Reis, Fábio Augusto Gomes Vieira [UNESP]; Spisila, André Luis; Nolasco, Marjorie Csekö (Springer Nature, 2022)
Fossils have great potential for elucidating and popularizing geosciences among all age groups. Brazil, due to its continental dimension and wide geodiversity, has many internationally important fossiliferous sites, which include rocks from the Pre-Cambrian to the Quaternary eras. Thus, in this study, we analyse the legislation and public policies related to the extraction, use, or protection of fossils and palaeontological sites in Brazil. This research examines the legal and infra-legal normative documents and numerous publications on the subject. Our results show that fossils are considered a heritage of the union, i.e. mineral heritage according to the mining code or, exceptionally, cultural heritage when they are related to human culture. Although the sale of fossils as a main product of mineral extraction is not regulated, it is possible and legal to sell material extracted from rocks formed basically by fossils. Hence, it is common to observe the use of such fossiliferous rocks as landfill, construction and paving materials, agricultural inputs, or other types of industrialized products. Mining and civil works, by exposing layers of fresh or slightly weathered rocks and expanding available observation areas, contribute to the advancement of palaeontological knowledge. Accordingly, we evaluate the absence of clear criteria for differentiating whether a fossil is a rare specimen or a common occurrence, entailing the necessity for the proposal of new norms for the preservation of Brazilian fossil heritage. Our study demonstrates that a new legal framework concerning the extraction of mineral resources is crucial to ensure a better preservation of Brazilian fossil heritage and to provide legal certainty for both professionals who research these natural assets and mining companies or those who develop construction projects in sedimentary basins.
Keywords: Brazil heritage; Fossils; Legislation